The role of stereotactic body radiation therapy in oligometastatic colorectal cancer: Clinical case report of a long-responder patient treated with regorafenib beyond progression. Issue 48 (December 2017) - Roberto, Michela; Falcone, Rosa; Mazzuca, Federica; Archibugi, Livia; Castaldi, Nadia; Botticelli, Andrea; Osti, Mattia Falchetto; Marchetti, Paolo
Abstract: Rationale: Regorafenib is the new standard third-line therapy in metastatic colorectal cancer (mCRC). However, the reported 1-year overall survival rate does not exceed 25%. Patient concerns: A 55-year-old man affected by mCRC, treated with regorafenib combined with stereotactic body radiotherapy (SBRT), showing a durable response. Interventions: After 6 months of regorafenib, a PET/CT scan revealed a focal uptake in a solid lung nodule which was treated with SBRT, whereas continuing regorafenib administration. Fourteen months later, the patient had further progression in a parasternal lymph node, but treatment with regorafenib was continued. The regorafenib-associated side effects, such us the hand-foot syndrome, were favorable managed by reducing the dose from 160 to 120 mg/day. Outcomes: Patient-reported outcome was characterized by a progression-free survival of approximately 3 years. Lessons: in presence of oligometastatic progression, a local SBRT while retaining the same systemic therapy may be a better multidisciplinary approach. Moreover, disease progression is no longer an absolute contraindication for continuing the regorafenib treatment.